Stem cells and new intervention measures as emerging therapy in cardiac surgery - Pisano, Calogera; Nardi, Paolo; Balistreri, Carmela; Altieri, Claudia; Bertoldo, Fabio; Ruvolo, Giovanni (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2020)
Cardiovascular disease (CVD) presents a great burden for elderly patients, their caregivers, and health systems. Structural and functional alterations of vessels accumulate throughout life, culminating in increased risk of developing CVD. Several inflammatory pathway are involved in vascular ageing. The growing elderly population worldwide highlights the need to understand how aging promotes CVD in order to develop new strategies to confront this challenge. In this review we analyzed the role of stem cells and new intervention measures as emerging drugs for vascular aging.